Nos habíamos terruqueado tanto: cómo y por qué el poder instrumentaliza el concepto “terrorismo” - Jordán, Rubén (2024)
This paper examines the discursive appropriation of the concept of “terrorism” by the contemporary establishment. Drawing some indications from the political philosophies of Plato and Hobbes, who share a similar enthusiasm for violence as an instrument of power, the argument is made that the misuse of the concept of “terrorism” functions as a mechanism for the self-legitimation and self-affirmation of power. This is the case because power, through widely disseminated doctrinal systems, presents terrorist acts as a sample of the hypothetical state of total chaos that would arise if its current configuration were modified.